(untitled) (Malaysian Management Journal, 2000)
A substantial body of evidence in management theory and business practice has accumulated to show that Strategic Human Resource Management (SHRM) is associated with improved organizational performance. In spite of this evidence, empirical studies have shown that some organizations are slow in implementing those practices. One of the fundamental reasons behind this is the fact that as a body of practical knowledge, SHRM has seemingly lacked any theoretical research framework to underpin it. Thus, this paper is an attempt to address this problem by (1) contributing to theory building in strategic HRM, and (2) empirically testing the hypothesis that SHRM practices affect productivity. This study used a sample of 129 managers of oil palm estates from a national survey of estate managers reflecting the 1998 financial year Using linear regression techniques, the results suggest that (1) estates implement less strategic HI? practices than anticipated, and (2) some strategic HR practices were related to productivity. Managerial implications of the study were discussed.